The Effects of Biomaterial Implant Wear Debris on Osteoblasts - Zhang, Li; Haddouti, El-Mustapha; Welle, Kristian; Burger, Christof; Wirtz, Dieter C.; Schildberg, Frank A.; Kabir, Koroush (Frontiers in Cell and Developmental Biology, 2020)
Aseptic loosening subsequent to periprosthetic osteolysis is the leading cause for revision of arthroplasty failure. The biological response of macrophages to wear debris has been well established, however, the equilibrium of bone remodeling is not only dictated by osteoclastic bone resorption but also by osteoblast-mediated bone formation. Increasing evidence shows that wear debris significantly impairs osteoblastic physiology and subsequent bone formation. In the present review, we update the current state of knowledge regarding the effect of biomaterial implant wear debris on osteoblasts. The interaction of osteoblasts with osteoclasts and macrophages under wear debris challenge and potential treatment options targeting osteoblasts are also presented.